PEMANFAATAN CITRA MODIS LEVEL 1B DALAM PEMBUATAN PETA PRAKIRAAN DAERAH PENANGKAPAN IKAN (Studi Kasus : Pantai Selatan Blitar) - Sukojo, Bangun Muljo; Febriani , Eva Resti; Febriani, Eva Resti (Departemen Teknik Geomatika ITS, 2017)
The potential of marine resources in Blitar quite large but utilization is not optimal, so it requires a Regional Forecast Map Fishing in order to exploit the potential of fishery resources there is more optimal. Determination of the area forecast use of the fish can be predicted from the parameters of sea surface temperature and chlorophyll-a. Modis image level 1b can be used in the manufacture of the forecast utilization of fish pennagkapan area. Used algorithm ATBD (Theoretical Basic Document Encryption Modis) 25 to determine sea surface temperature and Algorithms Morel 4 is used to determine the chlorophyll-a. The results obtained from this study is the RMSE test conducted between field data with the data Modis image of RMSE 1b level of 0.706568, with forecasts of fishing areas and potentially potent enough.